American digestion and indigestion - Adams, Bonnie Frances (My University, 1899)
Introduction: The centuries of abuse that the human stomach has had to endure are telling more and more, as each succeeding generation is born with all the weakness consequent to the abnormal conditions of its ancestors, and grows up under conditions even more unnatural than those which undermined the health of its forefathers: until now the organs which at first bore the burden that was thrust upon them without faltering, and struggled to defend man against the evils that inevitably come to avenge natures broken laws, worn out, too weak to battle yet living, struggle feebly on. The guards once down disease claims man its victim. The physician of today finds a harvest ripe before him, a harvest that if he be thoughtful he must deplore. ‘Tis not one nation alone, that suffers from this great evil. In every civilized land, can be found the results of an unhealthy digestive system in various forms of disease. Because American illness can be traced more directly to its source, and because Americans, by their fast living, aggravate the disease, perhaps it is, that we are called a nation of dyspeptics. Without entering into the question of whether other nations are not a much so we must admit that we are a dyspeptic people.
Citation: Adams, Bonnie Frances. American digestion and indigestion. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Dyspepsia; Physiology of Stomach; Healthful Dygestion; Theses; Manuscripts (documents)